Turkey’s Regional Powerhood Within Regional (In)Security Complex: Transformation From a Conflict-ridden Environment Into a Security Community - Dilek, Oguz; Iseri, Emre; Celik, Nihat (Journal of Regional Security, 2018)
Many optimists believed that the “Arab Spring” was a ripe moment for regional radiant Turkey with its pro-active stance that could trigger “demonstrative effect” and transform the conflict-ridden Middle Eastern (in) security complex into a pluralistic security community. However, those expectations on Turkey’s capabilities to transform the region have fallen short as Middle East re-entered into turmoil. In this light, the article aims to conduct an academic inquiry into the reasons that curtailed Turkey of priming the pump for a regional security community in the region. It argues that international system (structural), sub-systemic (regional), and finally that of agential factors (Turkey’s own domestic embodiment) hindered Turkey’s efforts to transform the Middle East into security community. It concludes that three main hindrances (that of systemic, sub-systemic and domestic) which altogether, but particularly the latter, render Turkey to fall short in restoring peace and stability back to the Middle East at the time of Arab uprisings.